Nonlinear dynamic of the transmembrane potential and pH along the cell membrane of Chara alga - A. I. Lavrova; T. Yu. Plusnina; A. V. Ukrainetz; Galina Yu. Riznichenko; Andrei B. Rubin (Компьютерные исследования и моделирование, 2009)
The model of potential dependent proton transfer trough the cell membrane of Chara alga developed in [1] is considered. In the last version of the model we considered two variables: proton concentration near the surface cell and transmembrane potential. In present version we introduce the new variable - proton concentration in cytoplasm. Oscillative and chaotic dynamic of transmembrane potential was obtained in calculations. The physiological role of these patterns is discussed.